Effects of silymarin on growth performance, antioxidant capacity and immune response in turbot (Scophthalmus maximus L.). Issue 6 (24th April 2019) - Wang, Jingyu; Zhou, Huihui; Wang, Xuan; Mai, Kangsen; He, Gen
Abstract: A 9‐week feeding trial was conducted using triplicate groups of turbot (6.50 ± 0.01 g) to explore the potential effects of silymarin. Three concentrations of silymarin (100, 200, and 400 mg/kg) were added to the plant protein‐based diet. Fish were randomly distributed into fiberglass tanks (30 fish per tank). The results showed that adding 100 mg/kg silymarin significantly improved the growth performance, with no effects on feed utilization. The antioxidant capacity in the liver was significantly improved in the 100 mg/kg and 200 mg/kg silymarin groups by not only inducing the activities of superoxide dismutase ( SOD ) and catalase but also increasing the messager RNA (mRNA) expression levels of SOD, glutathione peroxidase, and peroxiredoxin 6. Meanwhile, supplying 100 and 200 mg/kg of silymarin enhanced the heights of villi and enterocytes. Silymarin supplementation reduced the mRNA expression of interleukin‐8 and tumor necrosis factor‐α but induced the expression of transforming growth factor‐β ( TGF‐β ) in the intestine. These results indicated that silymarin was a potential nutraceutical that could enhance the growth performance and health status of turbot fed in a high plant protein diet. Adding 100 mg/kg silymarin to the plant protein diet achieved optimal performance in turbot.